2013
DOI: 10.1017/s0950268813002732
|View full text |Cite
|
Sign up to set email alerts
|

Influenza in hospitalized children in Ireland in the pandemic period and the 2010/2011 season: risk factors for paediatric intensive-care-unit admission

Abstract: Influenza causes significant morbidity and mortality in children. This study's objectives were to describe influenza A(H1N1)pdm09 during the pandemic, to compare it with circulating influenza in 2010/2011, and to identify risk factors for severe influenza defined as requiring admission to a paediatric intensive care unit (PICU). Children hospitalized with influenza during the pandemic were older, and more likely to have received antiviral therapy than children hospitalized during the 2010/2011 season. In 2010/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…A literature review by Havers et al supported this finding, concluding that children with neurological conditions were overrepresented among patients hospitalized with influenza [ 14 ]. An Irish study by Rebolledo et al, concluded that children with risk conditions had an increased risk for severe influenza [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A literature review by Havers et al supported this finding, concluding that children with neurological conditions were overrepresented among patients hospitalized with influenza [ 14 ]. An Irish study by Rebolledo et al, concluded that children with risk conditions had an increased risk for severe influenza [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seroprevalence data from Germany had already shown evidence for A(H1N1)pdm09 infection in as many as 25 % of children aged 1–4 years and 48 % of 5–17 year-old children for the pandemic season 2009/10 [ 26 ]. A similar shift towards younger hospitalized children [ 27 , 28 ] and towards younger children with severe paediatric A(H1N1)pdm09-associated influenza from the pandemic season to the first post-pandemic season had also been detected in other European countries [ 28 31 ].…”
Section: Discussionmentioning
confidence: 65%
“…Climate and other external factors have been demonstrated to be associated with trends in IMD in the literature [69,70]. Additionally, seasonal trends in respiratory viral infections (influenzae and RSV) for these two EY were also distinct to preceding years perhaps consistent with reduced levels of population contact [71,72].…”
Section: Discussionmentioning
confidence: 90%